Atrial fibrillation and kidney function: a bidirectional Mendelian randomization study. (23rd May 2021) - Park, Sehoon; Lee, Soojin; Kim, Yaerim; Lee, Yeonhee; Kang, Min Woo; Kim, Kwangsoo; Kim, Yong Chul; Han, Seung Seok; Lee, Hajeong; Lee, Jung Pyo; Joo, Kwon Wook; Lim, Chun Soo; et al.
Abstract: Aims: The aim of this study was to investigate the causal effects between atrial fibrillation (AF) and kidney function. Methods and results: We performed a bidirectional summary-level Mendelian randomization (MR) analysis implementing the results from a large-scale genome-wide association study for estimated glomerular filtration rate (eGFR) by the CKDGen ( N = 765 348) and AF ( N = 588 190) to identify genetic instruments. The inverse variance weighted method was the main MR method used. For replication, an allele score-based MR was performed by individual-level data within a UK Biobank cohort of white British ancestry individuals ( N = 337 138). A genetic predisposition to AF was significantly associated with decreased eGFR [for log-eGFR, beta −0.003 (standard error, 0.0005), P < 0.001] and increased risk of chronic kidney disease [beta 0.059 (0.0126), P < 0.001]. The significance remained in MR sensitivity analyses and the causal estimates were consistent when we limited the analysis to individuals of European ancestry. Genetically predicted eGFR did not show a significant association with the risk of AF [beta −0.366 (0.275), P = 0.183]. The results were similar in allele score-based MR, as allele score for AF was significantly associated with reduced eGFR [for continuous eGFR, beta −0.079 (0.021), P < 0.001], but allele score for eGFR did not show a significant association with risk of AF [beta −0.005 (0.008), P = 0.530]. Conclusions: Our study supports that AF is a causal risk factor for kidney function impairment. However, an effect of kidney function on AF was not identified in this study. Graphical Abstract: